Predicting School Leadership Interests in Parents of English Learners: An Exploratory Study. Issue 3 (8th August 2016) - Vera, Elizabeth; Heineke, Amy; Carr, Andrea; Camacho, Daniel; Israel, Marla Susman; Goldberger, Nancy; Clawson, Angela; Hill, Martin
Abstract : This study contributes to the literature on parent involvement by examining predictors of educational leadership interests of parents of English learners (ELs). Using a sample of 129 parents of ELs who represented diverse ethnic backgrounds, the researchers examined parent leadership interests with survey research. Parent leadership interests were significantly predicted by expectations for children's educational success, encouragement from teachers, and parents' own level of education. Specifically, parents with lower educational expectations for their children, who were encouraged to be involved by their children's teachers, and with higher levels of formal education were more likely to express leadership interests. These data have implications for how schools could extend outreach efforts to encourage participation of parents who may see themselves as less effective leaders.